Deferoxamine Interference in Fibro-inflammation: Additional Action in Control of Obese Adipose Tissue Dysfunction - Ferreira Gotardo, Erica M.; de Morais, Thaina Rodrigues; Timóteo Ferreira, Ana Paula; Rabelo e Paiva Caria, Cintia; Ribeiro, Marcelo Lima; Gambero, Alessandra (Current Drug Targets, 2023)
Introduction: Several studies demonstrated that deferoxamine, an iron chelator, can improve inflammatory alterations in adipose tissue induced by obesity. Obesity alterations in adipose tissue are also associated with tissue remodeling, and deferoxamine has anti-fibrosis action previously described in sites like the skin and liver. Methods: In this work, we analyzed deferoxamine effects on adipose tissue fibro-inflammation during obesity induced by diet in mice. in vitro approaches with fibroblasts and macrophages were also carried out to elucidate deferoxamine activity. Results: Our results demonstrated that in addition to exerting anti-inflammatory effects, reducing the cytokine production in adipose tissue of obese mice and by human monocyte differentiated in macrophage in vitro, deferoxamine can alter metalloproteinases expression and extracellular matrix production in vivo and in vitro. Conclusion: Deferoxamine could be an alternative to control fibro-inflammation in obese adipose tissue, contributing to the metabolic improvements previously described.
Keywords: extracellular matrix